2018
DOI: 10.1007/s40789-018-0213-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coal ash fusion temperatures using computational intelligence based models

Abstract: In the coal-based combustion and gasification processes, the mineral matter contained in the coal (predominantly oxides), is left as an incombustible residue, termed ash. Commonly, ash deposits are formed on the heat absorbing surfaces of the exposed equipment of the combustion/gasification processes. These deposits lead to the occurrence of slagging or fouling and, consequently, reduced process efficiency. The ash fusion temperatures (AFTs) signify the temperature range over which the ash deposits are formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Another direction of research is the use of machine learning methods to predict AFTs [11,[20][21][22][23][24][25][26][27][28][29]. The most frequently techniques used were artificial neural networks (ANNs) and support vector machine (SVM).…”
Section: Standard:iso Pn-iso 540:2001 Descriptionmentioning
confidence: 99%
“…Another direction of research is the use of machine learning methods to predict AFTs [11,[20][21][22][23][24][25][26][27][28][29]. The most frequently techniques used were artificial neural networks (ANNs) and support vector machine (SVM).…”
Section: Standard:iso Pn-iso 540:2001 Descriptionmentioning
confidence: 99%
“… Many studies have been conducted to predict the melting characteristic temperature of coal ash. Tambe et al used a computational intelligence model to estimate the coal ash melting temperature and obtained good results. Using the GWOSVM model, Xiao et al predicted the DT of coal ash and indicated that the model has a specific prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of extremely complicated and nonlinear phenomena can be modeled and studied using artificial neural networks (ANN), which are effective modeling and investigation methods. While having a pretty good level of prediction accuracy, some current AFT prediction models consider coal from various geographic regions . The models are complicated, costly, and time-consuming to test since they depend on a large number of predictors (input variables).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the viscosity–temperature characteristics of the coal ash, blending is a promising method , by which the high-melting-point mullite and quartz are transformed into the low-melting-point eutectics . Many researchers have established various models to find an empirical or statistical correlation between the ash fusion temperatures and ash composition. Sasi et al devised the prediction model using two approaches, namely, a thermodynamic approach using the ChemApp subroutine and a purely data-driven approach using artificial neural networks, obtaining a conclusion that a combination of these two approaches provided an efficient and reliable way toward the industrial application …”
Section: Introductionmentioning
confidence: 99%